Islamic Da’wah Methodologies and The Challenges Facing Da’wah in The Contemporary Society - Hamad Ambali (Indonesian Journal for Islamic Studies, 2025)
Background of study: Da’wah in the contemporary society is facing lots of challenges from both the callers and the called. This is as a result of the put up attitudes from both ends.Aims and scope of paper: The paper elucidates the Islamic da’wah methodologies which have been laid down in the Sharī‘ah of Islām in order to amend the da’wah approaches of the contemporary scholars and to warn the general public against turning away from the truth.Methods: In order to achieve the set objectives, the paper adopted analytical and phenomenological methods of research. The analytical methodology is used to explain the connotation of da’wah, the importance of da’wah and the Islamic da’wah methodologies while the phenomenological method is applied to elaborate the challenges of da’wah in the contemporary Nigerian society.Result: Findings have shown that the failure of da’wah is as a result of the approaches adopted by most of the contemporary callers, it has also been found out that many a caller has different motive from the Islamic general da’wah motives for going into da’wah activity.Conclusion: The paper concludes by recommending adequate Islamic knowledge for any intending caller so as to be able to prosper in his da’wah journey.